Konstruksi Teologi Persahabatan dari Tradisi Saroan di Toraja - Yawan Minaldi Paonganan (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
Toraja is widely known for its attractive cultural richness, which is preserved in Rambu Tuka and Rambu Solo. Toraja people see the term saroan as a community formed to strengthen social integration. This article, using qualitative methods and a descriptive phenomenological approach, aims to describe the phenomenon of friendship relations framed in the Saroan tradition. Data about saroan was collected through direct observation and semi-structured interviews, and a literature study was utilized to explore the theme of friendship. The research results found that friendship in saroan is lived by a moral bond that moves group members to be responsible and maintain the value of friendship in the act of mutual acceptance and respect (singga' sengkaran, siporannu, sipopa'di). The friendly relationship built in saroan goes beyond genealogical boundaries (rarabuku), as is also expressed in the book of Proverbs 17:17, about a friend who shows love at all times and becomes a brother in difficulties. Friendly relationships are built through openness and a willingness to give and receive. These values are the glue for harmonization in saroan.